Penerapan Terapi Diversional Pada Pasien Harga Diri Rendah di Wilayah Kerja Puskesmas Limboto Kabupaten Gorontalo - Vidya Salsabilla Taib; Nur Uyun I. Biahimo; Wiwi Susanti Piola; Firmawati Firmawati (Malahayati Nursing Journal, 2024)
ABSTRACT Low self-esteem is negative thoughts and feelings towards oneself so that sufferers feel a loss of self-confidence, pessimism and worthlessness in their lives..One intervention to support situational low self-esteem is diversional therapy. The aim of this research isidentifying self-esteem before and after being given diversional therapy to patients with low self-esteem in the working area of the Limboto Community Health Center, Gorontalo Regency. The research method used in this research is experimental design (one group pre-test post-test design). From the results of this research, it can be seen that the mean value of the pre test is 13.20 and the post test is 17.00, the standard deviation of the pre test is 000 and the post test is 422, the standard error of the pre test is 1.033 and the post test is 3.682, and the total data is 10 for the pre test and post, as well as the Sig value. 2-tailed is 0.002 0.05, meaning there is a significant influence between the pre-test and post-test. There is an influence of the application of diversional therapy on patients with low self-esteem at the Limboto health center, Gorontalo district. It is hoped that the results of this research can become a reference and add information about diversional therapy in patients with low self-esteem. Keywords: Low Self-Esteem, Diversional Therapy  ABSTRAK Harga diri rendah adalah suatu pemikiran dan perasaan negatif terhadap diri sendiri sehingga penderita merasakan hilangnya rasa percaya diri, pesimis dan tidak berharga dikehidupannya. Salah satu intervensi pendukung harga diri rendah situasional yaitu terapi diversional. Tujuan penelitian ini yaitu mengidentifikasi harga diri sebelum dan setelah diberikan terapi diversional terhadap pasien dengan harga diri rendah di wilayah kerja Puskesmas Limboto Kabupaten Gorontalo. Metode penelitian yang digunakan pada penelitian ini adalah experimental design (one group pre-test post-test design). Hasil penelitian ini dapat diketahui bahwa nilai mean pre test yakni 13,20 dan post test 17,00 standar devisiasi pre test yakni 000 dan post test 422, standar eror pre test 1,033 dan post test 3,682, serta jumlah data sebesar 10 untuk pre test dan post, serta nilai Sig. 2-tailed adalah 0,002 0,05 artinya terdapat pengaruh yang signifikan antara pre test dan post test.Terdapat pengaruh penerapan terapi diversional pada pasien harga diri rendah di puskesmas limboto kabupaten gorontalo. Diharapkan hasil penelitian ini dapat menjadi acuan dan menambah informasi tentang Terapi diversional pada pasien harga diri rendah. Kata Kunci: Terapi Diversional, Pasien, Harga Diri Rendah